Spiritual Care Competence in Nursing: Integrative Literature Review - Torres Contreras, Claudia Consuelo; Vargas Escobar, Lina María; Triana Rodríguez, Jorge Yecid; Cañon-Montañez, Wilson (Revista Cuidarte, 2023)
Introduction: Spiritual care can be considered a basic component of the philosophy of holistic care. Objective: Identify intervention studies with educational perspectives and strategies for developing spiritual care competencies in nurses and nursing students. Materials and methods: Integrative review of literature conducted in the period 2001-2021, in the databases PubMed, ProQuest, Scopus, LILACS, and VHL (Virtual Health Library). PRISMA statement guidelines were followed for the review, and it was based on Whittemore and Knafl’s stages for integrative reviews: problem formulation, literature search, evaluation of data, data analysis, and presentation of results. Results: Ten published intervention articles were found. Education for the development of spiritual care competencies has been provided by educational programs and activities in undergraduate nursing programs and with professional nurses in practice. Instructional strategies include specific courses, short sessions, or programs throughout the curriculum. Interventions have an impact on skills and knowledge. Students’ individual spirituality is a predictor of the competence to provide spiritual care. Conclusions: There is evidence of strategies to develop spiritual care competencies in nursing students and professionals, but publications on the subject are scarce. Therefore, implementing new and more rigorous strategies that allow the development of competencies for approaching spirituality in nursing is required.How to cite this article:  Torres Contreras Claudia Consuelo, Vargas Escobar Lina María, Triana Rodríguez Jorge Yecid, Cañon-Montañez Wilson. Competencia en cuidado espiritual en enfermería: Revisión integrativa de literatura. Revista Cuidarte. 2023;14(2):e2635. http://dx.doi.org/10.15649/cuidarte.2635
Keywords: Spirituality; Holistic Nursing; Education; Nursing; Nursing Research